La dimension métaphysique du devoir de mémoire. Prendre conscience de la nature humaine lors d’une visite à Auschwitz-Birkenau - Nathanaël Wadbled (Amnis)
The visit of the Auschwitz-Birkenau Memorial Museum is an experience concerning the duty of remembrance. It is then considered more as a practice than an idea or an injunction. Visitors interviewed in a research about their visiting experience refer to it as a metaphysical concern. Visitors consider human nature rather than as a historical, moral or political edification. This relationship to the past echoes the memory practice to which the philosopher Karl Jasper invites when he thinks about German guilt. Humans appear as both capable of committing horrors and capable of empathy with victims of horrors. These two mutually exclusive virtualities are respectively realized by the Nazis during the Shoah and felt by visitors during the Auschwitz-Birkenau visit. If the specter of horror haunts all humans and Humanity in general, the exercises of empathy by the victims may conjure it. On the one hand, the risk is not the return of the past, but the manifestation of this nature in another form. On the other hand, the responsibility to ensure that this kind of event does not happen again doesn’t mean not to be attentive to the non-reproduction of past political and ideological conditions, but rather to recognize the present human suffering.